DIGITAL MARKETING IN MSMES: BIBLIOMETRIC ANALYSIS - Rizal Muttaqin (Universitas Muhammadiyah Surakarta, 2023)
The Covid-19 pandemic has forced us to change marketing patterns to survive amid difficulties for MSMEs to face the impact of mobility restrictions in dealing with Covid-19. The intensity of consumers, and the flow of goods and services that have decreased resulted in reduced income. This condition makes business actors adopt digital technology in the transformation of marketing into digital marketing. The use of digital technology is needed for the sustainability of MSMEs to survive during the pandemic. The purpose of this study is to find out trends and research themes in digital marketing for MSMEs as well as to classify and identify literature themes and trends that are directly related to digital marketing and MSMEs over the last 7 years. This research method is bibliometric analysis, articles found from the Publish and Perish (PoP) software with a Scopus-indexed database. Of the 161 articles found from 2016 to 2022, 101 articles were analyzed in this study. The selected articles are then managed using Mendeley software. After managing the database, it is classified and visualized using VOSviewer software. Overall, this review provides an appropriate reference point for further research on digital marketing in MSMEs.